The legacy of colonial language policies and their impact on student learning: evidence from an experimental program in Cameroon - Laitin, David D.; Ramachandran, Rajesh; Walter, Stephen L. (Economic development and cultural change, 2019)
The relative educational returns on colonial versus indigenous language instruction in sub-Saharan countries have yet to be decisively estimated. To address this unanswered question, this paper provides an impact assessment of an experiment in Cameroon in which the first 3 years of schooling were conducted in a local language instead of in English. Test results in examinations in both English and math reveal that treated students exhibit gains of 1.1-1.4 of a standard deviation in grades 1 and 3 compared with the control students. It also increases the probability of being present in grades 3 and 5 by 22 and 14 percentage points, respectively. However, by the end of fifth grade, 2 years after reverting to the English stream, treated students still exhibit gains of 0.40-0.60 of a standard deviation, although the absolute scores for both groups are low enough to suggest limited learning is taking place.